Flexibilité alimentaire de bonobos en parc zoologique : consommation opportuniste d’espèces végétales autochtones et complément nutritionnel - Caroline Gérard; Flora Pennec; Jean-Pascal Guéry; Sarah Depauw; Geert Janssens; Mélissa Anne; Victor Narat; Bruno Simmen (Revue de Primatologie)
Understanding food selection and preference factors is a major challenge for species conservation, both in situ and ex situ, as it helps to improve the well-being of individuals housed in zoos. In bonobos (Pan paniscus), a species endemic to the Democratic Republic of Congo and classified as endangered by the International Union for Conservation of Nature (IUCN), little is known about these selection factors. Indeed, study sites in the wild are few and difficult to access and studies on these issues in captivity are rare. The aim of this study was to characterize the opportunistic food consumption of a community of 17 bonobos housed at La Vallée des Singes (Romagne, France) with access to a 0.8-hectare outdoor enclosure covered of local vegetation, in order to study the nutritional and ecological determinants of this behavior. Thanks to a multi-disciplinary methodology combining individual behavioral observations, botanical census, nutritional analyses (macro and micronutrients) and interviews with caretakers, this three-season study revealed the consumption of 46 foods belonging to 26 plant species, with significant seasonal variability. Bonobos seem to avoid the most fibrous food when availability in the enclosure allows it. This behavior seems to bring a nutritional supplement to the daily ration (particularly fiber and calcium), but also a behavioral enrichment, with a reduction of abnormal regurgitation-reingestion behaviors. This study, which complements those carried out in the wild to identify food selection mechanisms, highlights the importance of better understanding this behavior in zoos to improve the nutrition and well-being of the species housed there.